A new species of Validifemur Ma, Song & Zhu, 2007 (Lithobiomorpha, Lithobiidae) from northwest China - Yuhang Han; Sujian Pei; Huiqin Ma; Yaojun Li; Yinfeng Liu (Biodiversity Data Journal, 2022)
The myriapod fauna of China is still poorly known and very little attention has been paid to the study of Lithobiomorpha, with only more 100 species/subspecies hitherto known from the country, amongst which are only three species of Validifemur. Here we are describing a new species from northwest China.A new lithobiid species, Validifemur radispinipes sp. n., is described and illustrated from Wolong Mountain Park, Jingyuan County, Guyuan City, Ningxia Hui Autonomous Region, northwest China. The new species is compared with V. pedodontus Ma, Song & Zhu, 2007 from Shaanxi Province, China. Type specimens are deposited in the Institute of Myriapodology, School of Life Sciences, Hengshui University, Hengshui, China.